Fertility and Labor Market Responses to Reductions in Mortality - Sonia R. Bhalotra; Atheendar Venkataramani; Selma Walther (Institute of Labor Economics (IZA), 2018)
We investigate women's fertility, labor and marriage market responses to large declines in child and maternal mortality that occurred following a major medical innovation in the US. In response to the decline in child mortality, women delayed childbearing and had fewer children overall. Fewer women had three or more children, and a larger share remained childless. We present a new theory of the extensive margin response, premised upon improvements in child survival reducing the time women need to achieve their target number of children. This prompts fertility delay and labor market entry which, coupled with wage or fecundity shocks, can result in childlessness. Consistent with these predictions, we find that reductions in child mortality increased women's labor force participation, improved their occupational status and reduced their chances of ever having married. Maternal mortality decline had opposing effects on all of these outcomes.
Keywords: J13; I18; 330; women's labor force participation; fertility timing; childlessness; child mortality; maternal mortality; medical innovation